Viscous Dissipation and Suction characteristics of Heat and Mass Transfer past a Stretching Sheet. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
in this paper, we analyzed the effect of a suction and Soret number on heat and mass transfer Magneto Hydrodynamics (MHD) flow past an exponentially stretching sheet with the heat source/sink. Appropriate similarity transformations were employed to convert the governing partial differential equations to a set of highly non-linear ordinary differential equations, which was then solved numerically by Runga kutta sixth order method together with shooting technique. The Numerical results are obtained for the skin friction coefficient, Nusselt and Sherwood numbers for selected values of the governing parameters, such as the suction, magnetic field parameter  , viscous dissipation parameter  , heat generation parameter  , Schmidt number  , and the chemical reaction rate parameter  . Besides, it is obtained that the concentration profile decreases with an increment of the Schmidt number. A comparison was made with a previous study available in the literature and we found that it is in a good agreement.